KECERDASAN EMOSIONAL , IKLIM BUAYA ORGANISASI MENINGKATKAN KINERJA ORGANISASI PT ADIL MAKMUR - Rahayu Rahayu (KELOLA: Jurnal Ilmiah Manajemen, 2022)
PT. Adil Makmur strives to improve organizational performance with various strategies, especially strategies to increase human resources .To get to know about the performance of  PT Adil Makmur  the hypotheses that need to be answer are (1) the influence of  emotional intelligence toward improves   organizational performance  (2)  the influence of  organizational culture climate toward improves  organizational performance.  The study design used is a combination  of verificative statistic and descriptive research. , and data collection survey method with 75 employess of PT Adil Makmur, West Jawa, Indonesia as the  sample by using purpose sampling  technique and the   analisys tool  uses descriptive statistic average, and to answer the  hypotheses analisys tool uses  Sstruktural Eqution Method by using software Lisrel. The  result show on the descriptive analysis toward the variable used is positive and some are negative. The SEM result analysis toward the hypothesis test based on imphirical data of 2 hypotheses proven are  Emotional intelligence    is proven to be significantly influence   improves organizational performance, and organizational culture is proven to be significantly influence     improves  organizational performance